Methylprednisolone as an alternative therapy for Kawasaki disease: case series - Yudha Fadhol Arafah; Sasmito Nugroho; Noormanto Noormanto; Nadya Arafuri; Indah Kartika Murni (Paediatrica Indonesiana, 2020)
Kawasaki disease (KD), or mucocutaneous syndrome, is an acute, systemic vasculitis of small- and medium-sized arteries that predominantly affects patients younger than five years.1 KD is the leading cause of childhood acquired heart disease in the developed world.2 The incidence in those aged under 5 years varies widely throughout the world, accounting for 8.4 per 100,000 in the UK, 17.5 to 20.8 per 100,000 in the USA, and 239.6 per 100,000 in Japan.2 The diagnosis of classic KD is based on the simultaneous presence of high fever for 5 or more days with at least four of five other symptoms (bilateral conjunctival hyperemia, ulcerations of the lips and inflammation of the oral cavity, polymorphous rash, edema and desquamation of the extremities, and cervical lymphadenopathy), or fever associated with less than 4 of the diagnostic criteria and echocardiographic abnormalities of the coronary arteries.3